A new world: The metaverse - Doğan, Yunus; Yokak, Mehtap; Batdi, Veli (Nova Science Publishers, Inc., 2024)
The concept of the Metaverse has transcended its origins in science fiction to become a focal point of discussion and exploration in contemporary digital realms. This chapter provides a comprehensive examination of the Metaverse, encompassing its definition, historical trajectory, versions, and architectural structures. Beginning with an analysis of the definition of the Metaverse, the chapter navigates through its various interpretations, considering both its conceptual underpinnings and practical manifestations. Drawing upon a diverse array of sources, a nuanced understanding of the Metaverse is synthesized, elucidating its role as a virtual environment that facilitates immersive, interconnected experiences. The historical development of the Metaverse is then scrutinized, tracing its evolution from speculative narratives to tangible technological advancements. By exploring key milestones, such as the emergence of virtual reality platforms, online gaming communities, and social networking spaces, the chapter delineates the gradual convergence towards a cohesive Metaverse ecosystem. Furthermore, the chapter delves into the notion of "versions" within the Metaverse paradigm, recognizing the iterative nature of its evolution. From early conceptualizations to contemporary implementations, each version represents a distinct stage characterized by advancements in technology, user experience, and cultural integration. Through this analysis, insights are gleaned into the trajectory of future iterations, illuminating potential avenues for innovation and growth. Finally, the chapter investigates the architectural framework of the Metaverse, examining the underlying structures that facilitate its functionality and interactivity. In sum, this chapter offers a multifaceted exploration of the Metaverse, encompassing its conceptual foundations, historical evolution, versioned iterations, and architectural structures. By synthesizing diverse perspectives and insights, it contributes to a deeper understanding of this emergent digital domain and its implications for society, culture, and technology. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Metaverse; Metaverse architecture; Metaverse socialization; Versions of the metaverse